EARLY MEDIEVAL EASTERN PHILOSOPHY AND - Mustafayev Jafar Shomirzayevich; Islomov Bekzod Ilgʻor oʻgʻli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotatsiya: This article discusses early medieval Eastern philosophy and the Renaissance period. The term "Eastern philosophy" refers to the collection of philosophical movements and perspectives that originated in the continent of Asia. Eastern philosophy includes Indian, Chinese, Persian, Japanese, Korean, and Central Asian philosophy. Sometimes, Babylonian and Arab philosophy are also included in this list, although they are also relevant to Western philosophy.